Review of Ambient Air Pollution and Its Measurement along the River Basin - Porncharoen, Samart (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2021)
The elevated air pollutants in the regional atmospheric environment is a major problem that affects human health across the world particularly in the river basin. The river basin is important for social and economic development. This area is a good location for settlement and industrial estates as well as agriculture due to the availability of resources. This paper aims to present a detailed review of ambient air pollutants in the river basin as well as the mobile platforms for monitoring the air pollutants. While the measurements of the air pollutants using ship have been successfully demonstrated, there are some factors that interrupt the measurements such as power outages and unpleasant weather condition, reducing the reliability of the measurements. This paper suggests that an integration of the ship-based measurements with other mobile platforms may enhance this reliability.